Unlike Brief Inhibition of Microglia Proliferation after Spinal Cord Injury, Long-Term Treatment Does Not Improve Motor Recovery - Gaëtan Poulen; Sylvain Bartolami; Harun N. Noristani; Florence E. Perrin; Yannick N. Gerber (Brain Sciences, 2021)
Microglia are major players in scar formation after an injury to the spinal cord. Microglia proliferation, differentiation, and survival are regulated by the colony-stimulating factor 1 (CSF1). Complete microglia elimination using CSF1 receptor (CSF1R) inhibitors worsens motor function recovery after spinal injury (SCI). Conversely, a 1-week oral treatment with GW2580, a CSF1R inhibitor that only inhibits microglia proliferation, promotes motor recovery. Here, we investigate whether prolonged GW2580 treatment further increases beneficial effects on locomotion after SCI. We thus assessed the effect of a 6-week GW2580 oral treatment after lateral hemisection of the spinal cord on functional recovery and its outcome on tissue and cellular responses in adult mice. Long-term depletion of microglia proliferation after SCI failed to improve motor recovery and had no effect on tissue reorganization, as revealed by ex vivo diffusion-weighted magnetic resonance imaging. Six weeks after SCI, GW2580 treatment decreased microglial reactivity and increased astrocytic reactivity. We thus demonstrate that increasing the duration of GW2580 treatment is not beneficial for motor recovery after SCI.